Luteolin regulates the distribution and function of organelles by controlling SIRT1 activity during postovulatory oocyte aging - Xing, Xupeng; Peng, Jingfeng; Zhao, Jingyu; Shi, Ruoxi; Wang, Caiqin; Zhang, Zihan; Wang, Zihan; Li, Zicong; Wu, Zhenfang (Frontiers in Nutrition, 2023)
The quality of oocytes determines their development competence, which will be rapidly lost if the oocytes are not fertilized at the proper time after ovulation. SIRT1, one of the sirtuin family members, has been proven to protect the quality of oocytes during postovulatory oocyte aging. However, evidence of the effect of SIRT1 on the activity of organelles including the mitochondria, the endoplasmic reticulum (ER), the Golgi apparatus, and the lysosomes in postovulatory aging oocyte is lacking. In this study, we investigated the distribution and function of organelles in postovulatory aged oocytes and discovered abnormalities. Luteolin, which is a natural flavonoid contained in vegetables and fruits, is an activator of SIRT1. When the oocytes were treated with luteolin, the abnormal distribution of mitochondria, ER, and Golgi complex were restored during postovulatory oocyte aging. The ER stress protein GRP78 and the lysosome protein LAMP1 increased, while the mitochondrial membrane potential and the Golgi complex protein GOLPH3 decreased in aged oocytes, and these were restored by luteolin treatment. EX-527, an inhibitor of SIRT1, disrupted the luteolin-mediated normal distribution and function of mitochondria, ER, Golgi apparatus, and lysosomes.In conclusion, we demonstrate that luteolin regulates the distribution and function of mitochondria, ER, Golgi apparatus, and lysosomes during postovulatory oocyte aging by activating SIRT1.